Analysis of Trip Production and Attraction Model In Serang District - Budiman, Arief; Bethary, Rindu Twidi; Asy Syahid, Mushab Abdu; Fajri, Malisa Hanum; Abdurrohim, Abdurrohim (Jurnal Fondasi, 2024)
Serang Regency located on the northwestern of Java Island in Banten Province, with an annual population growth rate of 1,31%. The main economic sectors in this region are industry, plantations, and agriculture. Based on Central Bureau of Statistics report from 2015 to 2019, approximately 70% of Serang Regency's total land area is devoted to rice fields, horticultural, plantations, and fisheries, representing the predominant land use in the region. Population growth due to migration and natural growth will result an increase in the number of trips required by residents for their activities thus affecting the pattern of movements in the area. The purpose of this research is to identify factors that influence and to obtain a model of the generation and attraction in Serang Regency. The analysis used is multiple linear regression analysis with the type 1 stepwise method. Dependent variable used in this research are trip generation and attraction in Serang Regency, and there are 11 independent variables selected based on geographical, demographic, socioeconomic, land use, and transportation infrastructure parameters. The results showed that the factor of the total area of paddy fields (ha) (X10) and the variable number of schools (X4) have the most significant influence on trip generation of movements in Serang Regency with the selected model Y1 = 7113,807 – 1,505X10 + 93,999X4 with a value of R² = 0,812. Meanwhile, the factor that most influences attraction is the plantation area (ha) factor (X11) with the selected model Y2 = 10427,988 – 4,428X11 with a value R² = 0,828.